Psychometric properties of Basic Empathy Scale among female juvenile delinquents and school youths - Pechorro, Pedro Fernandes Santos (2017)
Research on empathy often distinguishes between affective and cognitive empathy, but there is limited knowledge regarding the application or measurement of these two dimensions of empathy among female youth, espe- cially forensic samples of female youth. The main aim of the present study was to examine the psychometric properties of the Basic Empathy Scale (BES) among a Portuguese sample of female youths (N = 377), composed of incarcerated female juvenile offenders (n = 103) and school youths (n = 274). The two-factor structure of the BES obtained a good fit among the school sample, but the fit among the forensic sample was poor. Both samples demonstrated adequate psychometric properties in terms of Cronbach's alpha, omega coefficient, mean inter-item correlations, corrected item-total correlation range, and criterion validity. However, some caution is advised when using the BES with female youth involved in the juvenile justice system, particularly with incarcerated female youth.